SYSTEMATICS LITERATUR REVIEW: PEMBELAJARAN MATEMATIKA DALAM MENINGKATKAN KEMAMPUAN METAKOGNITIF - Umroh; Novaliyosi; Mutaqin, Anwar (Jurnal Riset Pembelajaran Matematika, 2024)
This study aims to explore the influence of various mathematics learning models and learning media on improving students' metacognitive abilities in the learning process. By using the systematic literature review (SLR) method in this study using databases from Google Scholar and Scimago sources which will be reviewed from 2016-2024 with predetermined inclution criteria, so that 24 articles were selected in this research. The results of the analysis show that the integration of learning models can improve students' metacognitive abilities, such as problem based learning (PBL) and discovery learning. The use of media and teaching materials can also help mathematics learning to improve metacognitive abilities such as learning modules and technology-based learning media such as LKPD with the help of Geogebra, Microsoft Mouse Mischief, and GeoEnzo is very important in helping to improve students' metacognitive abilities. The integration of effective learning models and innovative learning media is essential for the development of students' metacognitive, which will ultimately improve the quality of learning and academic outcomes of students during the learning process.